(untitled) (مجلة ديالى للبحوث الانسانية, 2023)
Distance education is becoming more and more popular in higher stages of education in Iraq and it is increasingly preferred by the students from all age groups. In order to provide quality education, ministry of education and higher education institutions should be aware of students’ needs and expectations and, on this basis, to search for effective strategies and solutions for introducing distance education. The answer to the question: “Which factor has the highest weighted percentile on the perception of English?” has a significant role in taking students and instructors responses to the implementation of pedagogies used in online courses in the light of the six factors. Additionally, it might make it easier to accredit more distance learning programs at Open Educational College, which is most known for the phase of its educational model transition from face-to-face to online learning during the Covid-19 pandemic. In this paper, 15 students and four professors from the English language department at the Open Educational College in Jablah discuss the aspects related to online learning that have an impact on how English is perceived. The primary goal of the study is to ascertain how the six elements in e-learning courses affect students’ and instructors’ perceptions of English and how they are interrelated. The interactions between students’ perspectives and English department professors, as well as the experiences people have using technologies in both daily life and in educational settings, are examined. The academic community and everyone involved in the development, planning, and implementation of strategies and platforms for online learning would benefit from the conclusions reached.